Hidden Identity Conflict: Discourses of Heritage of the Grand Duchy of Lithuania in Lithuanian and Belarusian Internet Media (2013–2014) - Venckūnas, Valius (Information & Media, 2019)
[full article and abstract in Lithuanian; abstract in English]This article is aimed at presenting an insight into national identities as constructed on the basis of the heritage of the Grand Duchy of Lithuania (GDL) in the major Lithuanian and Belarusian news sites (2013–2014). By performing content analysis, it was revealed that in the vast majority of news publications, either Lithuania or Belarus, respectively by country of publishing, was considered as the main or only successor of the GDL, although this narrative was not elaborated upon and was seen as self-explanatory. The neighboring state was rarely criticized and its narrative mostly considered as frivolous and not worthy of attention. A lack of contact, discussion and mutual explanation between the Lithuanian and Belarusian narratives in the public sphere means that a conflict between both national identities can be seen as hidden or potential.
Keywords: GDL; Grand Duchy of Lithuania; Lithuania; Belarus; national identity; internet media